First case report of sepsis caused by Rhizobium pusense in Japan. (10th January 2018) - Kuchibiro, Tomokazu; Hirayama, Katsuhisa; Houdai, Katsuyuki; Nakamura, Tatsuya; Ohnuma, Kenichirou; Tomida, Junko; Kawamura, Yoshiaki
Abstract : Introduction. Species of the genus Rhizobium are opportunistic, usually saprophytic, glucose-non-fermenting, Gram-negative bacilli found in agricultural soil. Rhizobium pusense infections are the least common Rhizobium infections and have low incidence. Case presentation. Herein, we report the first case of sepsis with R. pusense in Japan in a 67-year-old Japanese woman with a history of hyperlipidaemia, hypertension, diabetes, hypothyroidism and osteoporosis. She had undergone cerebrovascular treatment because she was diagnosed with a subarachnoid haemorrhage. The results of postoperative blood culture showed oxidase-positive, urease-positive, non-lactose-fermenting Gram-stain-negative rods. Using the Vitek2 system, the isolate was distinctly identified as Rhizobium radiobacter . However, 16S rRNA gene sequencing showed 99.93 % similarity with the type strain of R. pusense and 99.06 % similarity with the type strain of R. radiobacter . Additional gene sequencing analysis using recA (97.2 %) and atpD (96.2 %) also showed that the isolated strain is most closely related to R. pusense . The patient was cured by treatment using intravenous meropenem (3 g/d) for 4 weeks and was discharged safely. Conclusion. The definite source of sepsis was unknown. However, the possibility of having been infected through the catheter during the cerebrovascular operation was speculated.